2011
DOI: 10.1177/0333102411421026
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-painful scalp arteries in children and adolescents suffering from migraine

Abstract: Scalp arteries are frequently painful on pressure in children and adolescents with migraine, both in the absence of and during a migraine attack. Painful arteries suggest hypersensitivity of periarterial nociceptive afferents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…With a stronger digital pressure (between 1.0 and 2.5 kg/cm 2 ), our group found that a large percentage of migraineurs have one or more scalp arteries painful to pressure, both during and in absence of a migraine attack (12). This is also the case in children and adolescents (13). As a control procedure we applied finger pressure alongside the arteries, which was significantly less efficacious.…”
Section: Presence Of Painful Points On Scalp Arteriesmentioning
confidence: 63%
See 1 more Smart Citation
“…With a stronger digital pressure (between 1.0 and 2.5 kg/cm 2 ), our group found that a large percentage of migraineurs have one or more scalp arteries painful to pressure, both during and in absence of a migraine attack (12). This is also the case in children and adolescents (13). As a control procedure we applied finger pressure alongside the arteries, which was significantly less efficacious.…”
Section: Presence Of Painful Points On Scalp Arteriesmentioning
confidence: 63%
“…the presence of pain-activating peptides. This is also present in a small percentage of healthy people (12,13). It should be noted that scalp muscles also frequently present pressure-painful points in migraine (14,15), and sometimes in healthy people (16).…”
Section: Presence Of Painful Points On Scalp Arteriesmentioning
confidence: 98%
“…There are research precedents for inducing pain in clinically ill youth for therapeutic and nontherapeutic purposes. In our literature search, and consistent with a prior literature review by Birnie et al (Birnie et al, 2014), we did not find appraisals of the acceptability of induced pain using a variety of protocols in youth with the following conditions: chronic pain in general (Evans, Tsao, & Zeltzer, 2008; Tsao, Evans, Seidman, & Zeltzer, 2012; Zeltzer et al, 2002); sickle cell disease (Gil et al, 2001; Gil et al, 1997; O’Leary, Crawford, Odame, Shorten, & McGrath, 2014); myofascial pain (Tsao et al, 2012; Zeltzer et al, 2002); fibromyalgia (Reid, McGrath, & Lang, 2005); complex regional pain syndrome (Tsao et al, 2012; Zeltzer et al, 2002); extracephalic tenderness (Metsahonkala et al, 2006); headache (tension) (Birnie et al, 2011; Ciabchett, Celeste Serci, Madeddu, Cossu, & Giuseppina Ledda, 2011; de Oliveira & Valenca, 2012; Evans et al, 2008; Fernandez-de-Las-Penas et al, 2010; Metsahonkala et al, 2006; Smith, Martin-Herz, Womack, & McMahon, 1999; Tsao et al, 2012); migraine (Ciabchett et al, 2011; de Oliveira & Valenca, 2012; Smith et al, 1999; Tsao et al, 2012; Zeltzer et al, 2002); arthritis (Gualano et al, 2010; Reid et al, 2005; Thastum, Zachariae, Scholer, Bjerring, & Herlin, 1997; Zeltzer et al, 2002); joint pain (Tsao et al, 2012); limb pain (Evans et al, 2008); back pain (Evans et al, 2008; Zeltzer et al, 2002); neck pain (Evans et al, 2008); chest pain (Zeltzer et al., 2002); neurovisceral pain (Tsao et al., 2012); recurrent and functional abdominal pain (Apley, Haslam, & Tulloh, 1971; Birnie et al, 2011; Dufton, Dunn, Slosky, & Compas, 2011; Dufton et al, 2008; Evans et al, 2008; Feuerstein, Barr, Francoeur, Houle, & Rafman, 1982; Tsao et al, 2012; Walker, Williams, Smith, Garber, Van Slyke, & Lipani, 2006; Walker, Williams, Smith, Garber, Van Slyke, Lipani, et al, 2006; Williams, Blount, & Walker, 2011; Zeltzer et al, 2002; Zohsel, Hohmeister, Flor, & Hermann, 2008); and surgical pain (Srikandarajah & Gilron, 2011). The perspectives of youth and their families concerning instigation of pain in these settings would be of inter...…”
Section: Discussionmentioning
confidence: 76%